How Can a Histidine Kinase Respond to Mechanical Stress? - Kenney, Linda J. (Frontiers in Microbiology, 2021)
Bacteria respond to physical forces perceived as mechanical stress as part of their comprehensive environmental sensing strategy. Histidine kinases can then funnel diverse environmental stimuli into changes in gene expression through a series of phosphorelay reactions. Because histidine kinases are most often embedded in the inner membrane, they can be sensitive to changes in membrane tension that occurs, for example, in response to osmotic stress, or when deformation of the cell body occurs upon encountering a surface before forming biofilms, or inside the host in response to shear stress in the kidney, intestine, lungs or blood stream. A summary of our recent work that links the histidine kinase EnvZ to mechanical changes in the inner membrane is provided and placed in a context of other bacterial systems that respond to mechanical stress.